Queer Representation in Honorio Bartolome De Dios’ Geyluv - Valenzuela, Christian Loid (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study focused on exploring the representation of queer identities and relationships using the main characters from Honorio Bartolome De Dios’ Geyluv. The study also investigated if reading LGBT fiction, like Geyluv, may influence the perception of the readers towards queer identities and relationships. Thematic analysis was utilized to create supporting codes and themes from the responses of the participants to come up with bases of analyzing the story using qualitative textual analysis. It was revealed that fluidity in relationship is prone to internal and external conflicts such as unreciprocated feelings, issues related to masculinity, gender stereotypes and discrimination as it entails someone to experience conflicts such as societal stigma, pressure, doubt, fear of rejection and lack of support. Furthermore, reading LGBT fiction may significantly influence the perceptions of individuals about queer identities and relationships. The study recommends involving more characters in different Filipino LGBT stories to have a more comprehensive documentation of the representation of queer identities and relationships